Empirical Analysis of the Impact of Immigration on European Labor Markets in Times of Economic Recession - Medková, Tatiana; Zouhar, Jan, 1982-; Arlt, Josef, 1962-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2019)
Immigration and its impacts are highly discussed topics in today's society. Several empirical studies have found either no negative impact of immigration on European economies, or only a negligible impact on the native employees. However, these studies were mostly done before the recession period, or do not distinguish between recession and expansion. We assume that the uncertainty on labor markets after 2008 together with growing prejudices about immigrants have created a new environment where immigration impacts and the immigrants’ position on European labor markets need to be reanalyzed.We focus on immigration impacts and the position of immigrants in 13 European countries in years 2011–2014. Our quantitative analysis is conducted at three different levels – countries, regions and individuals – and employs advanced econometric methods, e.g. panel-data models with two-way clustering, spatial panel data models or multi-level discrete-choice models.We found no evidence of immigration impacts on regional employment and unemployment rates even in times of economic recession in European union. However, our results suggest that immigrants have a different position on local labor markets, with a higher probability of being unemployed than natives. This impact is lower in capitals than in non-capital regions.
Vedoucí práce: Jan Zouhar
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: ekonometrie a operační výzkum [obor disert. práce]; disertace; dissertations